Diabetic older women without peripheral neuropathy amplify body sway but are capable of improving postural stability during a saccadic gaze task - Rodrigues, Sérgio Tosi [UNESP]; Delacosta, Thaís Cristina [UNESP]; Barbieri, Fabio Augusto [UNESP]; Paschoalino, Gabriel Palmeira [UNESP]; Gotardi, Gisele Chiozi [UNESP]; Barela, José Angelo [UNESP]; Monteiro, Henrique Luís [UNESP]; Bosqueiro, José Roberto [UNESP]; Polastri, Paula Fávaro [UNESP] (My University, 2023)
Background: Diabetic older people tend to present deteriorated performance in balance and locomotion activities, even those without peripheral neuropathy. There is evidence that saccadic eye movements are used to reduce body sway in young and older healthy adults, but it has not been shown that diabetic older people preserve this visuomotor adaptation capacity. Research question: Are diabetic older women without peripheral neuropathy capable of improving postural stability during a saccadic gaze task? Methods: Seventeen type 2 diabetic older women (68.2 ± 10.7 years old) and seventeen healthy women, age-matched controls (66.0 ± 8.4 years old) voluntarily participated in the study. All participants were instructed to stand upright, barefoot, as stable as possible, for 30 s. Participants maintained their feet parallel to each other, at standard and narrow bases of support, while either fixating on a stationary target (fixation condition) or performing horizontal saccadic eye movements to follow a target (eccentricity of 11° of visual angle), which continuously disappeared and reappeared immediately on the opposite side (saccade 0.5 Hz and saccade 1.1 Hz conditions). Results: Results indicated that the diabetic group clearly had deteriorated postural control, as shown by increased values of mean sway amplitude and mean sway velocity. However, diabetic and control groups were similarly capable of using saccadic eye movements to improve their postural stability, reducing their sway velocity compared to a gaze fixation condition. Significance: Diabetes per se (without peripheral neuropathy) amplifies postural sway of older women as compared to their healthy age-matched controls. However, diabetic older women without peripheral neuropathy are capable of improving postural stability during a saccadic gaze task.
Keywords: Diabetes; Older women; Postural sway; Saccades; Vision